Effects of the van der Waals Force on the Dynamics Performance for a Micro Resonant Pressure Sensor - Lizhong Xu; Yulei Liu; Xiaorui Fu (Shock and Vibration)
The micro resonant pressure sensor outputs the frequency signals where the distortion does not take place in a long distance transmission. As the dimensions of the sensor decrease, the effects of the van der Waals forces should be considered. Here, a coupled dynamic model of the micro resonant pressure sensor is proposed and its coupled dynamic equation is given in which the van der Waals force is considered. By the equation, the effects of the van der Waals force on the natural frequencies and vibration amplitudes of the micro resonant pressure sensor are investigated. Results show that the natural frequency and the vibrating amplitudes of the micro resonant pressure sensor are affected significantly by van der Waals force for a small clearance between the film and the base plate, a small initial tension stress of the film, and some other conditions.